Comparison of genre analysis approach and audio-lingual method in the teaching of discussion skills in the context of muet speaking examination - Hassan, Hafiza Aini; Habil, Hadina (2008)
Since the Malaysian University English Test (MUET) was introduced in 1999, the learners who wish to further their studies have to prepare themselves to sit for four papers – speaking, listening, reading and writing. Among all the papers, the learners are mostly intimidated by the speaking test. This is the paper which tests their speaking skills formally. This study will focus on two ways of teaching speaking skills – the Genre Analysis Approach and the Audio-lingual Method. The subjects will be form six students who are preparing to sit for the MUET tests. The subjects will be in two different groups, each will experience a different way of teaching – one via he Genre Analysis Approach, while another the Audio-lingual Method. The subjects’ responses will be analysed and compared. Finally in the conclusion, the researcher will be able to make recommendations of the strengths of the two ways and how the language teachers can adapt and adopt them to be utilised in their English Language classes, especially in teaching speaking.